Montelukast in the Treatment of Atopic Dermatitis: What is the Evidence? - Soares, Cristiana; Murteira, Diana; Santos, Maria (Gazeta Médica, 2023)
Atopic dermatitis is one of the most common chronic inflammatory skin diseases. Over the years, there has been some evidence regarding the involvement of leukotrienes in the pathophysiology of atopic dermatitis, and there are already reports of the use of montelukast in this pathology. The aim of this review is to assess the evidence regarding the efficacy of montelukast in the symptomatic improvement of atopic dermatitis. From the bibliographic research carried out, 56 articles resulted, of which 3 met the previously defined inclusion criteria. After analyzing the articles, is considered that there is no evidence of the effectiveness of montelukast in the symptomatic improvement of atopic dermatitis due to inconsistent findings between trials. More multicenter studies with larger samples and clear methodology are needed to clarify montelukast’s efficacy, adverse effects and long-term benefits.